High-Value Care Pediatric Curriculum - Suzanne Woods; Carolyn Avery; Kathleen Bartlett; William Bordley; Aimee Chung; Brian Eichner; Mikelle Key-Solle; Heather McLean; David Ming (Association of American Medical Colleges, 2015)
Abstract This series of seven modules provides a formal curriculum for pediatric residents and medical students in the concepts of high-value care (HVC). HVC aims to reduce unnecessary health care costs while still providing high-quality care for patients. This pediatrics curriculum has been adapted from the American College of Physicians and Alliance for Academic Internal Medicine HVC curriculum for internal medicine residents and republished with the permission of the American College of Physicians. This presentation has been successfully deployed as a morning report series for pediatric residents and medical students at a single institution. The use of an audience response system enhanced participation and received overwhelmingly positive feedback from the participants. The real-time survey results allowed pre− and posttest comparison of the participants' thoughts from the start to the end of a module. Participants also enjoyed working in small groups and practicing case-based learning. At the end of each module, they showed an interest in learning more about the subject matter and were challenged to see how the material would change their daily practice. Residents were more engaged in learning and understanding HVC with this educational series in both the inpatient and outpatient settings. Evidence-based guidelines are embedded in the modules to support clinical decision-making during case discussion. Work has also been started to develop collaborative models of education and expansion to departments including internal medicine, radiology, and emergency medicine at our institution.